Corporate foreign bond issuance and interfirm loans in China - Yi Huang; Ugo Panizza; Richard Portes (Graduate Institute of International and Development Studies, 2018)
This paper uses firm-level data to document and analyze international bond issuance by Chinese non-financial corporations and the use of the proceeds of issuance. We find that dollar issuance is positively correlated with the differential between domestic and foreign interest rates. This interest rate differential increases the likelihood of dollar bond issuance by risky firms and decreases the likelihood of dollar bond issuance of exporters and profitable firms. Moreover, and most strikingly, we find that risky firms do more inter-firm lending than non-risky firms and that this lending rose significantly after the regulatory shock of 2008-09, when the authorities sought to restrict the financial activities of risky firms. Risky firms try to boost profitability by engaging in speculative activities that mimic the behavior of financial institutions while escaping prudential regulation that limits risk-taking by financial firms.
Keywords: F34; F32; G15; G30; 330; China; bond markets in emerging markets; carry trade; shadow banking